The kinematics of Galactic disc white dwarfs in Gaia DR2. Issue 3 (21st January 2019) - Rowell, Nicholas; Kilic, Mukremin
ABSTRACT: We present an analysis of the kinematics of Galactic disc white dwarf (WD) stars in the solar neighbourhood using data from Gaia Data Release 2. Selection of WDs based on parallax provides the first large, kinematically unbiased sample of solar neighbourhood WDs to date. Various classical properties of the solar neighbourhood kinematics have been detected for the first time in the WD population. The disc WD population exhibits a correlation between absolute magnitude and mean age, which we exploit to obtain an independent estimate of the solar motion with respect to the local standard of rest. This is found to be ( U, V, W )⊙  = (9.5 ± 1.2, 7.5 ± 1.2, 8.2 ± 1.2) km s −1 . The UW components agree with studies based on main-sequence stars, however the V component differs and may be affected by systematics arising from metallicity gradients in the disc. The velocity ellipsoid is shown to vary strongly with magnitude, and exhibits a significant vertex deviation in the UV plane of around 15 deg, due to the non-axisymmetric Galactic potential. The results of this study provide an important input to proper motion surveys for WDs, which require knowledge of the velocity distribution in order to correct for missing low-velocity stars that are culled from the sample to reduce subdwarf contamination.